Konsep Mubadalah terhadap Relasi Suami Istri Pekerja dalam Pengasuhan Anak di Era Milenial: Studi Kasus Pasangan Pekerja di Kota Banda Aceh: Konsep Mubadalah Dalam Hukum Keluarga Islam, Relasi Suami Istri dalam Keluarga Islam, Konsep Mubadalah dalam Pengasuhan Anak di Era Milenial Pasangan Pekerja di Kota Banda Aceh - Fadhila, Dina (Medina-te : Jurnal Studi Islam, 2023)
The millennial era with various changes and challenges in parenting certainly colors the colors and models of parenting in each family. The importance of cooperation between husband and wife as workers in the family is one of the foundations for realizing resilience and childcare in the millennial era. The purpose of this study is as the basis for ideal parenting guidance in the realm of both parents who work outside the home today. This research uses field studies using qualitative descriptive research types based on cases that occur in the field. The data sources used in this study are primary data and secondary data. The results showed that the application of the concept of mubakan will greatly affect the relationship between husband and wife in child care and make both have their respective duties and live them well. So that the pattern of husband, wife relationships as workers outside but also has a role as parents in providing ideal child care in the current millennial era by placing the same relationship between husband and wife and as parents for their children.